The Nature of Culture as the Strength and Stability of Society: The Perspective of Islamic Religious Education - Ardianto Ardianto; St. Wardah Hanafie Das (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Culture is the main foundation that becomes strength and stability for society, because it contains values, norms, and traditions that form a collective identity. From the perspective of Islamic Religious Education (PAI), culture is seen as a strategic means to internalize Islamic values that support the creation of social and spiritual harmony. PAI plays a role in combining religious values with local cultural elements to build a society with character, ethics, and justice. In this context, culture is not only a heritage, but also a learning medium to strengthen solidarity, increase awareness of the importance of diversity, and maintain social stability. Thus, the synergy between culture and Islamic Religious Education is able to create a society that is based on noble values and resistant to the challenges of the times.